ANALISIS KOMPARASI KINERJA KEUANGAN SEBELUM DAN SESUDAH PENERAPAN PENGAKUAN PENDAPATAN BERDASARKAN PSAK 72 PADA PERUSAHAAN INFRASTRUKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hafizan Imanuddin; Anggraeni Yunita; Sumiyati (Accounting Journal of Ibrahimy (AJI), 2024)
The Financial Accounting Standards Board and the Indonesian Accountants Association issued PSAK 72 concerning Revenue from Contracts with Customers which adopted IFRS 15, as an adjustment to the previous standard which provides principles for recognizing company revenue. This adjustment provides a difference in the recognition of revenue value by having 5 stages of transaction analysis first based on contracts with customers. This difference has an impact on the company's revenue and profit recognition, as well as an influence on the company's financial performance. One of the companies affected is infrastructure companies, because there are several subsectors that are related to income from long-term contracts with customers and allow for combinations and contract modifications. The aim of this research is to test and analyze the differences in current ratio, debt to asset ratio, net profit margin and total asset turnover before the implementation of PSAK 72 (2017-2019) and after the implementation of PSAK 72 (2020-2022). The population in this research is infrastructure companies listed on the Indonesia Stock Exchange, with a research sample of 38 companies based on a purposive sampling technique. The analytical method used is the comparative descriptive method, using the analysis technique of the average difference test of two paired samples. The results of the research show that there are significant differences in the current ratio, net profit margin and total asset turnover, and there are no significant differences in the debt to asset ratio before and after the implementation of PSAK 72. There are consequences of implementing PSAK 72 which have an impact on liquidity and solvency risks. , profitability and effective use of company assets.